Petersen’s Hernia as a Complication of Bariatric Surgery: A Case Report - Dehghan, Pooneh; Ghanbari, Alireza; Khoshrou, Javad (Novelty in Biomedicine, 2021)
Background: Bowel obstruction due to Petersen hernia is a known but rare late complication of a R-Y surgery that can be a life threatening condition. Delayed intervention may result in a high morbidity and even mortality. The clinical findings are not specific, In this context, imaging exams have an important part in the early detection and surgery of this condition. Cases Report: We describe the case of a 46-year old man presenting with acute abdominal pain and a history of gastric bypass five years previously. Abdominal Ultrasound did not reveal any significant findings. Indeed, through the use of multi slice computed tomography with IV and oral contrast , diagnosis of internal hernia was made and confirmed by laparotomy. Conclusion:Internal hernias are rare and difficult to diagnose, but they should be included in the differential diagnosis in intestinal obstruction cases and a history of abdominal surgery to reduce the high morbidity and mortality rates; surgical intervention shouldn’t be delayed.